2008
DOI: 10.3171/jns/2008/108/2/0320
|View full text |Cite
|
Sign up to set email alerts
|

In vivo tracking of superparamagnetic iron oxide nanoparticle–labeled mesenchymal stem cell tropism to malignant gliomas using magnetic resonance imaging

Abstract: This study demonstrated that systemically transplanted MSCs migrate toward gliomas with high specificity in a temporal-spatial pattern, which can be tracked using MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 46 publications
5
100
0
1
Order By: Relevance
“…Specific migration of MSCs in the brain is well documented for lesion sites in the brain, 39,40 as well as in gliomas. [41][42][43] However, tracking MSCs in normal brains shows a variety of engraftment sites, ranging from the cerebellum to the forebrain. 44,45 Sites in which active neurogenesis occurs in adulthood, such as the hippocampus, subventricular zone and olfactory bulb, are often included in these preferred engraftment sites.…”
Section: Discussionmentioning
confidence: 99%
“…Specific migration of MSCs in the brain is well documented for lesion sites in the brain, 39,40 as well as in gliomas. [41][42][43] However, tracking MSCs in normal brains shows a variety of engraftment sites, ranging from the cerebellum to the forebrain. 44,45 Sites in which active neurogenesis occurs in adulthood, such as the hippocampus, subventricular zone and olfactory bulb, are often included in these preferred engraftment sites.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been suggested that mesenchymal stem cells (MSCs) may represent an alternative source of therapeutic stem cells (21,22). In experimental brain glioma models, intracranially implanted or intravenously injected MSCs can migrate away from the injection site toward tumor beds (23)(24)(25)(26)(27). Additionally, gene modification of MSCs with therapeutic cytokines clearly prolongs the survival of tumorbearing animals (23,25,28,29).…”
Section: Introductionmentioning
confidence: 99%
“…MRI and magnetic resonance spectroscopy are common imaging modalities for in vivo stem cell tracking in both preclinical and clinical settings (Hoehn, Kustermann et al 2002;Modo, Cash et al 2002;van den Bos, Wagner et al 2003;Kustermann, Roell et al 2005;Crowder, Brant et al 2006;Jansen, Shamblott et al 2006;Au, Lam et al 2007;Hsiao, Tai et al 2007;Magnitsky, Walton et al 2007;Partlow, Chen et al 2007;Politi, Bacigaluppi et al 2007;Suzuki, Cunningham et al 2007;Dash, Chan et al 2008;Himmelreich and Hoehn 2008;Kim and Song 2008;Terrovitis, Stuber et al 2008;Wu, Hu et al 2008;Kedzioreik, Ouwerkerk et al 2009;Kim, Huh et al 2009;Lythgoe 2009;Reekmans, Tambuyzer et al 2009;Solanky, Chung et al 2010;Tseng, Shih et al 2010;Chien, Hsiao et al 2011). Extraordinary three dimensional and anatomic resolution and high safety profile are the main advantages.…”
Section: Mrimentioning
confidence: 99%